Psychospiritual Therapy: An Essential Approach for Mental Health - Siti Nurjanah, Dian; Ratnawaty Chotim, Endah; Nursaadah, Olvia (UIN Sunan Gunung Djati Bandung, 2025)
In modern times, humans benefit from various technological advancements that make life easier, but these advancements are often accompanied by increasingly complex life challenges. For some individuals who struggle to adapt to these challenges, there can be negative impacts on their physical and mental health. Current medical and psychological treatments are often insufficient to address these issues fully, as achieving holistic health also requires a religious approach closely connected to mental well-being. This article explores various psychospiritual therapies that incorporate ritual worship practices commonly performed by Muslims. The research method employed is a library research or literature study approach, utilizing existing studies and related documents. The findings reveal that mental health and religion are deeply interconnected. To achieve mental health, a religious approach is essential. Worship rituals practiced by Muslims, such as ablution, prayer, supplication, and fasting, have been shown to serve as alternative therapies that not only improve physical health but also have a significant positive impact on mental health